Exploring Narrative and Coping Strategies of Osteosarcoma Survivors in China: A Qualitative Study - Ziqi Peng; Suet Lin Hung; Kwok Kin Fung (Cancer Reports)
ABSTRACT Background The existing studies have pointed out that cancer survivorship experiences significantly contribute to a comprehensive understanding of cancer survivors and insights into oncological care development. However, little is known about the long‐term survivorship experiences of osteosarcoma survivors within the Chinese context. Objective This study aims to explore osteosarcoma survivorship and coping strategies to enrich our understanding of the unique challenges and psychological needs of this population. Methods A qualitative narrative inquiry was used to provide a comprehensive understanding of survivors' illness narratives and coping strategies during osteosarcoma survivorship. Twelve osteosarcoma survivors were recruited using purposeful sampling. The data were collected through narrative inquiry interviews, which were audio‐recorded and transcribed. A thematic narrative analysis is used to interpret the narrative inquiry data. Results Three themes of illness narratives were identified, including “No one knows: chaos,” “Rethinking: restitution,” and “Restarting and retelling: quest.” Coping strategies encompassed in the subthemes indicated the importance of archive efforts of osteosarcoma survivors in questing post‐traumatic identity, values, and reconnecting to the community. Alternative narratives that emerged beyond the illness narrative framework highlighted contextual‐specific insights. Conclusion This study demonstrates that a narrative approach provides an alternative perspective for exploring the cancer survivorship experience. The findings underscore the evolving nature of illness narratives, highlighting the long‐term need for ongoing psychological support for osteosarcoma survivors. Moreover, the study highlighted a comprehensive understanding of osteosarcoma survivorship within the Chinese context. Specifically, it emphasizes (1) the rethinking of current medical discourse and psycho‐oncology practice within the Chinese context and (2) the narrative empowerment of bone cancer survivors. These findings have significant implications for expanding exploration into the nuanced experiences and identification of barriers to the integration of medical and psychological support among Chinese cancer survivors.